Analisis Framing Pemberitaan Media Online Tribun Sulbar. com Pasca Gempa Sulbar 2021 - Azis, Suandi; Fathiyah; Muhtar (Communication and Islamic Broadcasting Studies IAIN Parepare, 2023)
The presence of online media plays a role in providing information quickly during a disaster and after a disaster. Online media plays an important role in framing information that can educate audiences about disaster mitigation through the principles of disaster journalism. This type of research is qualitative research that is built based on framing analysis according to Zhongdang Pan and Gerald M. Kosicki. This qualitative research procedure produces descriptive data. Data collection is done by observation and documentation. Data analysis was carried out by analyzing Tribun Sulbar.com news according to Zhongdang Pan and Gerald M. Kosicki's framing model which consists of 4 structural devices, namely syntax, script, thematic and rhetorical, then conclusions are drawn from the data. The study results show that Tribun Sulbar.com has fulfilled the four framing structures of Zhongdang Pan and Gerald M. Kosicki: syntactic, script, thematic, and rhetorical devices. Tribun Sulbar.com highlights the government's efforts in post-earthquake recovery by taking only one point of view from the government. Tribun Sulbar.com has carried out the functions of the media, namely the function of information, education, and social control. The online media Tribun Sulbar.com carries out a mitigation and preventive role with the news it produces. The news narrative of Tribun Sulbar.com contains short paragraphs.